2019
DOI: 10.1021/acs.joc.9b00231
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Divergent Benzo[b]fluorenones through Cycloaromatization Reactions of 1,5-Enynols and 1,5-Diynols

Abstract: A facile and efficient synthesis of divergent benzo­[b]­fluorenones is described through the use of dichlorobenzoquinone-promoted oxidative cycloaromatization reactions of acyclic 1,5-enynols and 1,5-diynols. The success of these cascade reactions depends on the chemoselectivity of the initial Meyer–Schuster rearrangement to produce allenol intermediate, which is followed by regioselective Schmittel cyclization and the subsequent Friedal–Crafts alkylation or radical attack at the terminal Ar moiety. Only an ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…A little later, the same group established that a similar process was possible starting from alkene derivatives 131 . In that case, two equivalents of DDQ were used [78b] …”
Section: Cascade Reactions Starting By a Meyer Schuster Rearrangementmentioning
confidence: 99%
“…A little later, the same group established that a similar process was possible starting from alkene derivatives 131 . In that case, two equivalents of DDQ were used [78b] …”
Section: Cascade Reactions Starting By a Meyer Schuster Rearrangementmentioning
confidence: 99%
“…47,48 To explore functional group compatibility, we further used 4-iodoacetophenone (19) as a substrate. We were pleased to observe that the coupling product, 4-(propyn-1yl)acetophenone (20), was isolated in 82% yield ( Table 2, entry 5), and no reaction at the carbonyl group was observed. Under similar conditions, methyl 2-iodobenzoate (21) gave 85% yield of methyl 2-(propyn-1-yl)benzoate (22) (entry 6).…”
Section: Paper Syn Thesismentioning
confidence: 99%
“…12 It has been suggested that this cross-coupling reaction is difficult to achieve with lithium acetylides using catalytic amounts of palladium, because the highly nucleophilic alkynyllithiums may displace the ligands (e.g., PPh 3 , Cl -) from the palladium complexes, forming lithium palladates that do not exhibit any catalytic activity. 13 O-Substituted arylalkynes are very useful intermediates in the synthesis of heterocyclic compounds 14 such as phthalides and isocoumarins, 15 furocoumarins, 16 2-substituted benzofurans, 17 indoles, 18 1,2-benzothiazine 1,1-dioxides, 19 benzoisothiazoles, benzofluorenones, 20 dihydroisobenzofuranes, 21 and isoquinolones. 14 Specifically, 1-propynylarenes that can be obtained by the above alkynylation protocols using prop-1-yne, are not only very valuable synthetic intermediates, but are also present as key motifs in a wide number of natural products, 22 many of which have important biological activity.…”
mentioning
confidence: 99%
“…In 2004, Carlos Saa and colleagues reported an intramolecular dehydro DA cycloaddition of diarylacetylenes where thermal cyclization of 1‐[2‐(arylethynyl)phenyl]‐3‐trimethylsilylpropynones 75 underwent rearrangement in notable switching between benzo[b]fluorenones and benzo[c]fluorenones yielded a mixture of products, including benzo[ b ]fluorenones 78 and benzo[ c ]fluorenones 79 that have immense bioactivity and necessity in organic synthesis (see Scheme 12). [122–124] The formation of benzo[b]fluorenones 78 via 80 arises from direct aromatization‐isomerization of the initial [4+2] cyclized product whereas, benzo[c]fluorenones 79 via 81 governed by six electron electrocyclic ring opening followed by aromatization‐isomerization with promising yields up to 93% as depicted in Scheme 12. The remarkable switch between benzo[b]‐ and benzo[c]fluorenones expedient during [4+2] cycloaddition pathway was one of the prominent accomplishments in the history of organic synthesis pursuits.…”
Section: Selectivity In Diels‐alder Cycloaddition Pathwaymentioning
confidence: 99%